The Applicative Constructions in Javanese Dialect of Kudus - Noor Malihah (PAROLE: Journal of Linguistics and Education, 2016)
This paper presents applicative constructions in Javanese Dialect of Kudus (or JDK for short). For Kudus people, Indonesian has become the favored language and JDK is considered inferior. This situation discourages the study of dialect. Therefore, a corpus was constructed in a fieldwork, sampling three genres: spontaneous conversation, elicited spoken narratives, and newspaper articles. The results indicate the existence of two constructions, one marked by –i and one marked by either standard –(a)ke or dialectal –na. Generally–i occurs more frequently than –na and –(a)ke, but the relative prominence of the other two markers –naand –(a)ke is not consistent. This might be a genre effect that occurs in these corpora. There appears to be a conscious selection of the dialect-marked form –na by the writer of the articles who ignores the use of –(a)ke.This study also demonstrates that adult speakers use –na twice as frequently as do the youngers. By contrast –(a)ke is used more frequently by younger speakers than adults. The marker –i is used with approximately the same frequency by both groups. However, the preference of the younger for the standard variant is highly suggestive despite not being significant.